2012
DOI: 10.1111/jai.12022
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary data on elasmobranch gillnet fishery in the Gulf of Gabès, Tunisia

Abstract: Summary Elasmobranchs are an important catch component in Tunisian artisanal fisheries. Generally, species‐specific information is largely unavailable for artisanal fisheries; an increase in knowledge thereof is essential to ensure proper management of these species. The study analyzed the gillnet fishery elasmobranch catches in the Gulf of Gabès, whereby 45 fishing trips were conducted from April to June 2007 and 2008 for the capture of a total of six species: three Rajiformes and three Carchariniformes. Rhin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…In the central Mediterranean, the three species were reported to be very common along the Tunisian, Maltese and west Sicilian shelves during the 1960s and 1980s (Bourgois & Farina, ; Quignard & Capape, ; Ragonese, Vitale, Dimech, & Mazzola, ) and around Libyan waters until the 1990s (Lamboeuf, ). Recent data show that the MUSP are still targeted by local artisanal fisheries using gillnets (Echwikhi, Saidi, Bradai, & Bouain, ) and also represent one of the main by‐catch species of longlines and trawl fisheries (Bradai et al, ). A decreasing trend in their annual catches was, however, observed during the 1990s (Bradai et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the central Mediterranean, the three species were reported to be very common along the Tunisian, Maltese and west Sicilian shelves during the 1960s and 1980s (Bourgois & Farina, ; Quignard & Capape, ; Ragonese, Vitale, Dimech, & Mazzola, ) and around Libyan waters until the 1990s (Lamboeuf, ). Recent data show that the MUSP are still targeted by local artisanal fisheries using gillnets (Echwikhi, Saidi, Bradai, & Bouain, ) and also represent one of the main by‐catch species of longlines and trawl fisheries (Bradai et al, ). A decreasing trend in their annual catches was, however, observed during the 1990s (Bradai et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…1, 2, 3). This is extremely surprising considering the very high productivity of the Gulf of Gabès, one order of magnitude higher than that of surrounding waters (Drira et al 2010), which attracts high numbers of other marine predators such as sharks and turtles (Echwikhi et al 2012(Echwikhi et al , 2013, and is home to one of the major Mediterranean artisanal fisheries (Jabeur et al 2000). Also, similar GPS tracking of Scopoli's shearwaters from the island of Linosa, located in the middle of the strait of Sicily, showed that those birds do use waters South of Linosa extensively, and never ventured East towards Zembra (Cecere et al 2013).…”
Section: Discussionmentioning
confidence: 95%
“…In the Mediterranean, it has been reported from France (Capapé et al 2006) Italy (Tortonese, 1956), Morocco (Lloris and Rucabado, 1998), Tunisia (Mejri et al 2004;Echwikhi et al 2013), Turkey (Iskenderun Bay: Başusta et al 2012), andIsrael (Ben-Tuvia, 1953;Golani, 1996) whereas its occurrence is rarely documented along the Hellenic and Anatolian coasts of Aegean Sea, and to date only a few records from Rhodes Island (Corsini-Foka, 2009) and Izmir Bay (Akyol and Capapé, 2014) are known (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its commercial interest, overfishing of mature females (that are aplacental viviparous and not prolific) poses a threat for resilience and conservation of this species (Echwikhi et al 2013). Therefore, it is listed as "endangered" according to the IUCN Red List of Threathened Species (IUCN, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation